Effects of ingredient and whole diet irradiation on nursery pig performance - Woodworth, J.C.; Webster, M.J.; James, B.W.; Real, D.E.; DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to determine the effects of irradiation of individual ingredients or the whole diet on growth performance in nursery pigs. The response was similar for both trials with pigs fed diets containing irradiated spray-dried animal plasma or soybean meal having increased (P<0.05) ADG compared with pigs fed the control diet with no irradiated ingredients or the complete diet that was irradiated. Also, ADFI (P<0.05) was higher for pigs consuming the diet with irradiated soybean meal compared with those fed the irradiated whole diet. Pigs fed irradiated spray-dried animal plasma also had superior F/G (P<0.05) compared with those fed diets containing irradiated microingredients or if all ingredients had been irradiated before manufacturing. Therefore, irradiation of certain feed ingredients can improve growth performance in nursery, whereas irradiation of all ingredients in the diet or the whole diet does not enhance performance.
Keywords: Swine; Nursery pig; Feed ingredients; Irradiation